SDF1-CXCR4 Signaling Maintains Central Post-Stroke Pain through Mediation of Glial-Neuronal Interactions - Yang, Fei; Luo, Wen-Jun; Sun, Wei; Wang, Yan; Wang, Jiang-Lin; Yang, Fan; Li, Chun-Li; Wei, Na; Wang, Xiao-Liang; Guan, Su-Min; Chen, Jun (Frontiers in Molecular Neuroscience, 2017)
Abstract: Central post-stroke pain (CPSP) is an intractable central neuropathic pain that has been poorly studied mechanistically. Here we showed that stromal cell-derived factor 1 (SDF1 or CXCL12), a member of the CXC chemokine family, and its receptor CXCR4 played a key role in the development and maintenance of thalamic hemorrhagic CPSP through hypoxia inducible factor 1α (HIF-1α) mediated microglial-astrocytic-neuronal interactions. First, both intra-thalamic collagenase (ITC) and SDF1 injections could induce CPSP that was blockable and reversible by intra-thalamic administration of both AMD3100 (a selective CXCR4 antagonist) and inhibitors of microglial or astrocytic activation. Second, long-term increased-expression of SDF1 and CXCR4 that was accompanied by activations of both microglia and astrocytes following ITC could be blocked by both AMD-3100 and YC-1, a selective inhibitor of HIF-1α. AMD-3100 could also inhibit release of proinflammatory mediators (TNFα, IL1βand IL-6). Increased-expression of HIF-1α, SDF1, CXCR4, Iba1 and GFAP proteins could be induced by both ITC and intra-thalamic CoCl2, an inducer of HIF-1α that was blockable by both HIF-1α inhibition and CXCR4 antagonism. Finally, inhibition of HIF-1α was only effective in prevention, but not in treatment of ITC-induced CPSP. Taken together, the present study demonstrated that in the initial process of thalamic hemorrhagic state HIF-1α up-regulated SDF1-CXCR4 signaling, while in the late process SDF1-CXCR4 signaling-mediated positive feedback plays more important role in glial-glial and glial-neuronal interactions and might be a novel promising molecular target for treatment of CPSP in clinic.